Pengaruh Segmenting Dan Targeting Terhadap Strategi Pemasaran Permen Jahe Cantik Pada Pd. Tasacika - Saepul Rohmat; Ashrul Tsani; Neneng Kartika Rini (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2020)
This research aims to find out the influence of Segmentation and Targeting on The Marketing Strategy of Beautiful Ginger Candy PD. Tasacika Sukabumi Regency. The analysis of the data used is a descriptive type with an exoplanatory method. Data collection techniques with interview methods, questionnaires, and observations. Based on the results of the research the influence of segmenting on marketing strategies, the influence of segmenting and targeting on marketing strategies, and the influence of targeting on loyalty marketing strategies. So it can be inferred from the research shows that the positive and significant influence between Segmenting and Targeting simultaneously on marketing strategies on Beautiful Ginger Candy in PD. Tasacika means that Segmenting and Targeting have an important role to play in creating more effective and efficient marketing strategies for the company.